Answer:
9.48
Step-by-step explanation:
Complete question
<em>A stainless steel patio heater is a square pyramid. The length of one side of the base is 89.6 The slant height of the pyramid 90.1. What is the height of the pyramid?</em>
To get the height of the pyramid, we will use pythagoras theorem.
slant height l is the hypotenuse
length of the base is the adjacent
height of the pyramid is the opposite
According to the theorem;
l² = h² + b²
90.1² = h² + 89.6²
8,118.01 = <em>h²+</em>8,028.16
h²= 8,118.01 - 8,028.16
h² = 89.85
h =√89.85
h = 9.48
Hence the height of the pyramid will be 9.48
<em>Note that the value of the slant height was assumed to solve the problem</em>.
Answer:
128 banana's... I would work it all out for u but the teacher just came in my room and had a go
Answer:
14,000 visitors weekly
Step-by-step explanation:
Break the Equation Down.
10^3 = 10 x 10 x 10
10x10x10=1000 V
Put the 1000 within the problem.
2 x 1000
Solve
2 x 1000 = 2000 Visitors
7 days are within a week so multiply the daily visitors (2000) by 7
2000 x 7 = 14,000
Answer: 14,000 visitors weekly
Hope you like this way of solving! Let me know if have any questions!
The expression which represents the other factor, or factors, of the given polynomial is option (C) (2x-1)(x+1)
A cubic equation in algebra is a one-variable equation of the form ax3+bx2+cx+d=0 where an is nonzero. The roots of the cubic function defined by the left side of this equation are the solutions to this equation.
Given expression 2x³-3x²-3x+2 whose one of factor is (x-2)
We have to find second factor of given equation
First we will be rational root theorem to given expression so will get following expression:
![\left(x+1\right)\frac{2x^3-3x^2-3x+2}{x+1}](https://tex.z-dn.net/?f=%5Cleft%28x%2B1%5Cright%29%5Cfrac%7B2x%5E3-3x%5E2-3x%2B2%7D%7Bx%2B1%7D)
So one factor is (x-1) and now simplifying
we get 2x² - 5x +2 and the factor of 2x² - 5x +2 will be (2x-1)(x-2)
Hence the expression which represents the other factor, or factors, of the given polynomial is option (C) (2x-1)(x+1)
Learn more about Polynomial here:
brainly.com/question/4142886
#SPJ10
Answer:
-7.5
Step-by-step explanation:
Simplify
-4b - 5 + 2b = 10
-2b - 5 = 10
-2b = 15
b = -7.5